Mechanical performance of polypropylene-enriched concrete: Insights into mechanical properties and strengthening with Jute FRP - Qudeer Hussain; Peem Nuaklong; Hafiz Waheed Iqbal; Fawad Ahmed Najam; Panumas Saingam; Chatpan Chintanapakdee (Results in Engineering, 2026)
• This study investigates the mechanical performance and strengthening potential of concrete incorporating polypropylene (PP) plastic aggregates as a partial replacement for natural coarse aggregates. • Two types of PP aggregates were utilized to account for potential differences in texture. • The experimental program evaluated workability, water absorption, compressive strength, elastic modulus, splitting tensile strength, flexural capacity, and failure modes of PP-modified concrete. • Results indicated a reduction in strength at higher replacement levels, accompanied by altered crack propagation and enhanced deformation capacity. • To compensate for strength loss and enhance structural performance, Jute Fiber Reinforced Polymer (JFRP) was applied as an external strengthening material. • JFRP confinement changed tension-controlled cracking in beams and brittle crushing in cylinders into ductile failure. The growing environmental impact of plastic waste and the depletion of natural aggregates have driven the development of sustainable concrete alternatives. This study investigates the mechanical performance and strengthening potential of concrete incorporating two types i.e., white and black of polypropylene (PP) plastic aggregates as a partial replacement for natural coarse aggregates, up to 15% by volume. The experimental program evaluated workability, water absorption, compressive strength, elastic modulus, splitting tensile strength, flexural capacity, and failure modes of PP-modified concrete. Results from the un-strengthened specimens indicated a reduction in strength at higher replacement levels, accompanied by altered crack propagation and enhanced deformation capacity. Compressive strength decreases with the increment of plastic aggregate replacement. The strength of white plastic aggregate mixture at 15 % reduced by 45% as compared to control specimens. To compensate for strength loss and enhance structural performance, Jute Fiber Reinforced Polymer (JFRP) was applied as an external strengthening material. Cylindrical specimens were confined using one and two JFRP layers, while beam specimens were wrapped at the tension face with similar layer configurations. The strengthened samples demonstrated significant improvements in compressive and flexural behavior, with notable enhancement in post-peak response, crack control, and ductility. The compressive strength of the 15% volume fraction PP aggregate replacement group decreased by 45% (white PP) and 34% (black PP) compared to the control group. However, after being confined by double-layer jute fiber reinforced polymer (JFRP), the compressive strength of the 5% white PP replacement group increased by 76%, and the flexural strength reached a maximum of 8.09 MPa .The failure modes of control cylinders and beams were brittle whereas the failure modes of JFRP specimens were ductile. The effectiveness increases as the number of layers increased.
Keywords: Innovative concrete reinforcement materials; Structural Behavior of Reinforced Concrete; Natural Fiber Reinforced Composites